Optimization of Integrated Reservoir for Supporting the Raw Water Supply - Shafur Bachtiar; Lily M. Limantara; Moh. Sholichin; Widandi Soetopo (Salehan Institute of Higher Education, 2023)
This research intends to analyze the optimal operation pattern for fulfilling the raw water demand, and it is conducted in the integrated cascade reservoir of Duriangkang-Muka Kuning, Batam City, Indonesia. However, Batam City is the economic center of the Riau Islands and absolutely needs enough raw water supplies to support its development. The need for raw water in Batam City is predicted to reach about 6,630.29 l/s in 2025. Due to the population growth that is estimated to reach about 1.8 million people in 2025 and the plan of Batam City development as an industry and tourism center, Batam City is faced with the condition that reservoir management becomes a very important thing for supporting the continuity of water supply. The methodology consists of collecting the supporting data, such as inflow, reservoir capacity curve, and data on water needs; then building the optimization model by determining the objective function and constraints of the integrated reservoir; and carrying out the optimization model by using linear programming and simulation models for the integrated reservoir operation. The result presents optimal reservoir operation of the integrated Duriangkang-Muka Kuning reservoirs. The reservoir operation consists of the boundary curve of upper and lower normal operation, the outflow for fulfilling the water need, and the rule of supply pumping from Duriangkang reservoir to Muka Kuning reservoir. It is hoped that the result can be used as a reference in operating the two reservoirs to fulfill the water needs of the Batam City population. Doi: 10.28991/CEJ-2023-09-04-07 Full Text: PDF